Encountering Buddhism : Western psychology and Buddhist teachings - Segall, Seth Robert (SUNY series in transpersonal and humanistic psychology., 2003)
"Creatively exploring the points of confluence and conflict between Western psychology and Buddhist teachings, various scholars, researchers, and therapists struggle to integrate their diverse psychological orientations - psychoanalytic, humanistic, cognitive-behavioral, transpersonal - with their diverse Theravada and Mahayana Buddhist practices. By investigating the degree to which Buddhist insights are compatible with Western science and culture, they then consider what each philosophical/psychological system has to offer the other. The contributors reveal how Buddhism has changed the way they practice psychotherapy, choose their research topics, and conduct their personal lives. In doing so, they illuminate the relevance of ancient Buddhist texts to contemporary cultural and psychological dilemmas."--Jacket